(3bVGjG OhdjI (B:s (3GdCReI GdYGdejI (B/s - (3MSjf, YOfGf GdSjOs ((3HjQhJ(B: s (3GdeDSSI GdLGeYjI(B, s, 2010)
(3GdGWGQ GdYGdej ddCReI , CSHGHG GdCReI GdYGdejI h WHjYJgG , GVWQGHGJ h NSGFQ aj GdCShGb GdYGdejI , UYhO eLehYI GdYTQjf , GdOhdI GdJONdjI h JQGLY GddjHQGdjI GdLOjOI , eMGhQ Gdbhi h GdahVi GdOhdjI (B.s
(3eQGLY U(B.117s
Keywords: (3GdCReI GdYGdejIs; (3GdeTcdGJ GdEbJUGOjIs